THE POSITION AND ROLE OF GENDER EQUALITY IN ISLAMIC VIEW - Faisal Abdullah (PSGA LP2M IAIN Pontianak, 2020)
Abstract Gender issues are essentially demanding the equality of male and female roles. Gender Ais the inherent nature of women and men in social and cultural construction. As long as justice exists, Gender problems are not a problem. Women are often considered weak who can not do anything and men are considered strong and can do anything. Gender is often interpreted as gender, but there are fundamental differences between them. Therefore , gender differences become good for both men and women as complementary, to know each other and to give each other compassion and a sense of security in their souls. . In the view of society that women are a delicate and gentle and emotional and shy creature, whereas men are depicted with a strong, harsh, loud and assertive figure, enterprising, rational and courageous. In general Islam does not deny the similarities between men and women in terms of obtaining equal rights . Islam gives the teaching of the Ummah to give the highest respect and position for a woman . This paper discusses how Islam gives a position on the rights of equality to women, both in the role of social society and in the political scene. And it has been demonstrated by the Prophet in societal life. Surely without sacrificing his main task as a child educator even in the same time he can pursue his career outdoors . The woman getskan a special position compared to men, the position is, among others: Sama with a man's position, the position of the woman as the mother is higher than the male degree; Got part in the inheritance; The women of Santris had the priority of heaven from any door; Protecting the honors of women; Then for the parents who have daughters and their prodiation with affection and gentleness. The role of women in the social world of society takes many major roles. Women have the role of the most important existence in the future life of the nation's generation. Women who have a religious education will be able to distinguish and can discern which is good in Islam and which is not good in Islam. The existence of women in the midst of the family can give rise to the responsibility of a man in defending and maintaining and caring for the environment of the family from the influence or interference of outside parties. The role of women in male success also becomes evident that the various roles of women cannot be underestimated Keywords: Gender equality in Islamic view, position and role.